THE EFFECT OF SUBMAXIMAL EXERCISE ON THE ATTENTION OF HEALTHY ADULTS - D, Kartikasari (FAKULTAS KEDOKTERAN UNIVERSITAS KATOLIK WIDYA MANDALA SURABAYA, 2024)
Introduction. Submaximal exercise uses intensity below 85% of the predicted maximum pulse for age. One example of a submaximal exercise is the Three-minutes step test (TMST) which is practical, easy to implement in the subject's routine, and has clear measurement standards. After TMST is done, VO2max can be calculated which is the main indicator used to determine cardiorespiratory capacity. There have been no studies evaluating the effect of submaximal exercise and VO2max on domain attention in healthy adults.Aim. This study aim to evaluate effect submaximal exercise on the attention of healty adults.Material and method. Using a controlled before-and-after study, sixty healthy adults, aged 25-40 years, were divided into control and intervention groups (TMST). Attention function was measured with SDMT (Symbol Digit Modalities Test) before and after TMST or 3 minutes rest.Result. There was a significant difference in the intervention and control groups (p values <0.001 and 0.0029). The values of SDMT in the intervention group with the control group were significant with the p-value is <0.0001. The effect of the TMST intervention on SDMT was significant, with p values <0.0001.Conclusion. Submaximal exercise can improve attention function in healthy adults.